The Truths We Hold : an American journey - Harris, Kamala, 1964- ([New York, NY] : Penguin Books, 2020)
The autobiographical memoir of the first woman, African American, and South Asian American to become attorney general of the State of California, and the second black woman ever elected to the United States Senate. Harris discusses the impact that her family and community had on her life, and how she came to discover her own sense of self and purpose.
For the people -- A voice for justice -- Underwater -- Wedding bells -- I say we fight -- We are better than this -- Every body -- The cost of living -- Smart on security -- What I've learned.
new book 2024 fall.
Includes bibliographical references and index.
Keywords: Harris, Kamala, -- 1964-; Harris, Kamala, -- 1964- -- Political and social views; United States. -- Congress. -- Senate -- Biography; United States. -- Congress. -- Senate; African American women legislators -- Biography; Legislators -- United States -- Biography; Attorneys general -- California -- Biography; Public prosecutors; Public prosecutors; National characteristics, American; Justice, Administration of -- Political aspects -- United States; African American women legislators; Attorneys general; Justice, Administration of -- Political aspects; Legislators; National characteristics, American; Political and social views; Politics and government; Public prosecutors; United States -- Politics and government -- Philosophy; California; California -- San Francisco; United States; Autobiographies; Biographies